Enhancing visual working memory encoding: The role of target novelty - Mayer, Jutta S. (2011)
Perceptual salience improves the encoding of information into visual working memory (WM). However, the factors that contribute to this facilitation effect are not well understood. This study tested the influence of target familiarity on WM encoding. In each trial, participants were presented with either one or three targets and asked to encode their locations into WM. In Experiment 1, target familiarity was manipulated by presenting either an upright (familiar target) or upside-down (unfamiliar/novel target) A. Increasing the novelty of the targets led to improved performance in the spatial WM task. Experiment 2 showed that participants were faster in responding to novel versus familiar targets in a spatial detection task. Experiment 3 demonstrated that the beneficial effect of target novelty on WM encoding was not driven by differences in low-level features. Our results suggest that target novelty enhances the processes required for WM encoding, just as it facilitates perceptual processing.